Case Studies of Implementing Embedded Control System Framework on Autonomous Vehicle - Pikner Heiko; Karjust Kristo (E3S Web of Conferences)
This paper presents an embedded control system framework for developing Autonomous Vehicles (AVs). The framework offers a structured approach to designing, validating, and verifying vehicle hardware and software components, focusing on low-level control components. Leveraging Model-Based Design (MBD) with continuous testing, the framework facilitates early detection and correction of design flaws. Its versatility is demonstrated through experimental use cases on different types of autonomous ground vehicles.